Conservatism, Earning Management of Firm Values: Good Corporate Governance Moderating Variable - Diyah Santi Hariyani; Chindy Fadila; Putri Oktovita Sari; Sawal Sartono; Dwiati Marsiwi (Universitas Pendidikan Ganesha, 2022)
Increasing the company's value is the most crucial goal of the company. The value of a company is the company's performance and is reflected in the stock price. The share price is formed from the demand and supply of the capital market and considers the public's assessment of the company's performance. This study aims to analyze the influence of conservatism, earning management on company value with good corporate governance as a moderation variable. The research sample used a purposive sampling technique with a total sample of 52 manufacturing companies listed on the Indonesia Stock Exchange for the 201 8-2020 period. Using SmartPLS 3.0 with data analysis methods, namely convergent validity tests, descriptive validity, composite reliability, Cronbach's Alpha, goodness tests and path coefficient tests. The results of this study show that conservatism has a positive and significant effect on the company's value. GCG moderates the influence of conservatism on corporate value. Earning management has a positive and significant effect on the company's value. GCG moderates the influence of Earning Management on Company Value. This result can mean that good corporate governance can strengthen company values if the company uses conservatism and earning management practices. It can also be beneficial in increasing the value of the company.